Managing dangerous pathogens: challenges in the wake of the recent West African Ebola outbreak. Issue 1 (1st January 2016) - Abayomi, Akin; Katz, Rebecca; Spence, Scott; Conton, Brian; Gevao, Sahr M.
Abstract: In the aftermath of the 2014–2016 West Africa Ebola outbreak, there are a multitude of Ebola samples that are unaccounted for as well as virus samples stored in facilities that do not have an appropriate level of biosecurity and biosafety, creating serious threats to public health and security. In this article, we review the existing global governance mechanisms for addressing this biosafety and biosecurity concern. We also describe an ongoing effort to support the Government of Sierra Leone to find and secure Ebola samples as foreign labs are shut down, and institute systems for biosafety and biosecurity. We describe the challenges of tracking all Ebola samples and their associated data, and efforts to place these samples in suitable inventoried repositories by local health authorities. We recommend that governments around the world ensure that plans, procedures and regulations are in place prior to the chaos of an emergency in order to ensure that dangerous pathogens are handled in safe and secure manners, that data are preserved for research, and appropriate practices are utilised for consent.